2005
DOI: 10.1042/bj20041291
|View full text |Cite
|
Sign up to set email alerts
|

Separation of native prion protein (PrP) glycoforms by copper-binding using immobilized metal affinity chromatography (IMAC)

Abstract: The conformational conversion of the normal cellular prion protein (PrPC) into the pathology-associated PrPSc isoform is a key event in TSEs (transmissible spongiform encephalopathies). The host PrPC molecule contains two N-linked glycosylation sites and binds copper under physiological conditions. In contrast with PrPC, PrPSc is insoluble in non-ionic detergents and does not bind to Cu2+ ions. Hence, we utilized copper binding to separate and characterize both PrP isoforms. Infected and uninfected murine brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…The specificity of these antibodies has previously been reported. 21,22 We confirmed further the specificity of the PrP antibodies in our laboratory using Western blots of purified PrP C . All other primary antibodies are shown in Supplementary QImaging, Burnaby, BC, Canada) was used for fluorescence imaging.…”
Section: Materials and Methods Animalssupporting
confidence: 59%
“…The specificity of these antibodies has previously been reported. 21,22 We confirmed further the specificity of the PrP antibodies in our laboratory using Western blots of purified PrP C . All other primary antibodies are shown in Supplementary QImaging, Burnaby, BC, Canada) was used for fluorescence imaging.…”
Section: Materials and Methods Animalssupporting
confidence: 59%
“…In addition, steel 410L incubated with the RML strain To get an idea of whether the binding of PrP Sc to the metals was ionic in character or not, we used a metal ion-chelating pulldown assay (metal ions immobilized to Sepharose gel). Undigested PrP derived from RML-infected cells was bound to chelating Sepharose loaded to Cu 2+ and Ni 2+ in accordance with previous studies (Brown et al, 1997;Hornshaw et al, 1995;Muller et al, 2005;Shaked et al, 2001;Stockel et al, 1998;Taraboulos et al, 1992) (data not shown). Copper ions are known to bind to PrP C at the Nterminal octarepeat region, which can bind up to four Cu 2+ (Burns et al, 2003; Wells et al, 2006).…”
supporting
confidence: 72%
“…Another unexpected finding in this study was the retention of nondenatured PrP Sc by the copper ion, because failure to bind to immobilized copper ion has been reported by others to be a distinctive trait of nondenatured PrP Sc (56,57). In our experimental conditions, the binding of both FL PrP Sc and PrP res was reproducible, and plainly ion-dependent (data not shown).…”
Section: Figure 8 Mouse Prpmentioning
confidence: 61%